Kualitas Perairan Kanal Sungai Jawi dan Sungai Raya Dalam Kota Pontianak Ditinjau dari Struktur Komunitas Mikroalga Perifitik - Irwan Lovadi, Andriansyah, Tri Rima Setyawati, (Universitas Tanjungpura, 2014)
Sungai Jawi and Sungai Raya Dalam canals were frequently benefited by communities for a variety of daily necessities. These activities led to changes in water conditions and disrupt community structure in it. The purpose of this study was to determine the periphytic micro-algae community structure and the level of water pollution in Sungai Jawi and Sungai Raya Dalam canals. The samples were collected in Sungai Jawi and Sungai Raya Dalam canals. The determination of stations was based on environmental setting. Each canal was divided into 4 stations with 3 points laying substrate. The results showed that the periphytic micro-algae were from 3 divisions and 3 classes, namely Chrysophyta (Bacillariophyceae), Chlorophyta (Chlorophyceae), and Cyanophyta (Cyanophyceae). There were 26 genera of periphytic micro-algae in Sungai Jawi Canal and 25 genera of periphytic micro-algae in Sungai Raya Dalam Canal. Total abundance of periphytic micro-algae in Sungai Jawi Canal was 378,15 - 651,86 ind/cm2 and in Sungai Raya Dalam was 488,50 - 657,13 ind/cm2. The highest abundance was found in the both canal from the Bacillariophyceae class, Navicula genus. Shannon-Winner diversity index on Sungai Jawi and Sungai Raya Dalam canals was classified as middle category (2,0393 - 2,5690). Pollution level that occurred on both canal was still relatively mild.